Preliminary Results: Can Dual-Energy Computed Tomography Help Distinguish Cardiogenic Pulmonary Edema and Acute Interstitial Lung Disease?. Issue 1 (January 2018) - Takeuchi, Hitoshi; Suzuki, Shigeru; Machida, Haruhiko; Ishikawa, Takuya; Ueno, Eiko
Abstract : Objective: We compared iodine concentration in pulmonary ground-glass opacity on iodine density images of contrast-enhanced chest dual-energy computed tomography (DECT) between patients with cardiogenic pulmonary edema (CPE) and acute interstitial lung disease (AILD). Methods: Five of 12 patients who underwent contrast-enhanced chest DECT to exclude pulmonary embolism were clinically diagnosed with CPE and 7, with AILD. We compared the mean CT value on monochromatic images at 65 keV and iodine concentration on iodine density images between the affected and normal areas. Results: The mean iodine concentrations were comparable between the affected and normal areas ( P = 0.3048) in patients with CPE and were significantly higher in the affected than in the normal areas in those with AILD ( P < 0.0001). Conclusions: Measurement of iodine concentration in pulmonary ground-glass opacity of contrast-enhanced chest DECT has the potential to help distinguish CPE and AILD.